Google Trends Analysis of SIMKAH Search Patterns as an Indicator of Digital Transformation in Indonesian Marriage Registration Services - Novitasari; Dhyptya Ratri Anggraheni; Annisa Rosyidatuzzahra; Dhika Saputra (Srawung: Journal of Social Sciences and Humanities, 2026)
Digital transformation in public services has driven significant changes in public information-seeking behavior and the utilization of technology-based government services. This study analyzes search trends for the SIMKAH application through Google Trends on Web and YouTube platforms over the period 2019 to 2024, as an indicator of digital transformation in Indonesian government marriage registration services. Using a quantitative descriptive approach based on Google Trends secondary data, the analysis identifies search patterns by time, platform, and geographic region. The findings indicate a shift from text-based to video-based information-seeking behavior, reflecting changes in digital literacy and technology adoption. The Web platform dominated during 2019 to 2021 as a formal information medium, while YouTube recorded sustained growth from 2022 to 2024 as a tutorial and visual learning source. Geographic analysis shows that provinces in Sumatra and Sulawesi recorded the highest search interest on both platforms. These trends confirm Rogers' diffusion of innovation stages, whereby public adaptation to digital government services occurs through different platforms according to literacy levels and informational needs. Critically, search volume is interpreted as a behavioral proxy rather than a direct measure of service adoption. The study recommends multiplatform communication strategies integrating official textual content with community-based video tutorials to accelerate digital transformation in Indonesian government marriage registration services.